Economic Valuation of Ecosystem Services of National Zoological Park, New Delhi - Lele, Yatish; Sharma, Jitendra Vir; Yadav, S. P.; Sharma, Priya; Priyanka; Ghosh, Sonali (Indian Forester, 2020)
The National Zoological Park, New Delhi, is an ecologically significant park which, apart from its primary function in education and research, serve as natural habitats for free ranging animals. The present study was to assess the total annual economic value o f the key ecosystem services provided by the National Zoological Park, which includes employment generation, carbon storage and sequestration, education and research, recreational and cultural and biodiversity conservation. The one time value ofcarbon storage and surrogate value o flan d were also estimated in the study but not considered in the total annual economic value. The total economic value o f the ecosystem services provided by the National Zoological Park for 2019-20 was estimated to be INR 4227.99 million. Recreational and cultural service had maximum contribution o f 77% followed by education and research service which contributed to 9% o f the total annual value. Employmentgeneration contributed to 8% followedbybiodiversityservice which contributed to 6% and Carbon sequestration contributed 0.31%. The one time value for carbon storage and surrogate value o flan d was estimated to INR 171.5 million and INR 250 million. This makes an important case for the preservation o f the habitats such as the Zoological Park in contributing towards local, national, and global values.